Trade shocks, credit reallocation and the role of specialisation: Evidence from syndicated lending - Isabella Müller (Halle Institute for Economic Research (IWH), 2020)
This paper provides evidence that banks cut lending to US borrowers as a consequence of a trade shock. This adverse reaction is stronger for banks with higher ex-ante lending to US industries hit by the trade shock. Importantly, I document large heterogeneity in banks' reaction depending on their sectoral specialisation. Banks shield industries in which they are specialised in and at the same time reduce the availability of credit to industries they are not specialised in. The latter is driven by low-capital banks and lending to firms that are themselves hit by the trade shock. Banks' adjustments have adverse real effects.
urn:nbn:de:gbv:3:2-124569
Keywords: F14; F65; G21; 330; trade liberalisation; credit supply; sector specialisation; real effects